2013
DOI: 10.1016/j.intimp.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic amino alcohols reduces carrageenan-induced paw edema and anti-OVA DTH in BALB/c mice

Abstract: The inflammation process is a coordinated response of the organism related to immune response with release of pro-inflammatory substances, as nitric oxide, TNF-α and IL-1β. In this work, a series of lipophilic amino alcohols were evaluated on RAW264.7 and primary macrophages for the modulation of nitric oxide and TNF-α. The most potent compounds were submitted to the treatment of BALB/c mice and evaluation of the carrageenan-induced paw edema and TNF-α and IL1-β release in the paws and anti-OVA delayed type hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…DTH was induced in mice by challenging the footpad of previously sensitized mice with OVA as described previously [ 45 ]. In brief, C57BL/6 mice were sensitized by intradermal injections of 1 mg/ml CFA-emulsified OVA peptide (grade V) in a final volume of 200 μl at the tail base and back.…”
Section: Methodsmentioning
confidence: 99%
“…DTH was induced in mice by challenging the footpad of previously sensitized mice with OVA as described previously [ 45 ]. In brief, C57BL/6 mice were sensitized by intradermal injections of 1 mg/ml CFA-emulsified OVA peptide (grade V) in a final volume of 200 μl at the tail base and back.…”
Section: Methodsmentioning
confidence: 99%
“…The intraplantar CG injection also induces the edema formation in the paw and it has been fully characterized in the past showing acute inflammation by vasodilatation, exudation of protein-rich fluid and cell migration, primarily neutrophils, into the side of injury [24,29,30]. In this study, we have attempted to demonstrate the effects of CT on the CG-induced mouse paw edema and the results showed that all doses of CT presented antiedematogenic activity.…”
Section: Discussionmentioning
confidence: 91%
“…This activation facilitates the translocation of NF–κB into the nucleus, where it binds with its response element, which then activates the expression of genes of several proinflammatory mediators [ 20 ]. During the state of chronic inflammation, these proinflammatory mediators are produced abundantly, initiating pathogenesis of the onset of numerous inflammatory disorders [ 21 ]. Moreover, LPS-stimulated macrophages lead to the phosphorylation of MAPK signaling proteins, including ERK1/2, JNK, and p38, which result in excessive secretion and expression of inflammatory mediators and proteins, including NO, TNF-α, and IL-6, as well as the expression of iNOS and COX-2.…”
Section: Discussionmentioning
confidence: 99%